2019
DOI: 10.1093/ehjci/jez203
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between non-invasive myocardial work indices and main parameters of systolic and diastolic function: results from the EACVI NORRE study

Abstract: Aims The present study sought to evaluate the correlation between indices of non-invasive myocardial work (MW) and left ventricle (LV) size, traditional and advanced parameters of LV systolic and diastolic function by 2D echocardiography (2DE). Methods and results A total of 226 (85 men, mean age: 45 ± 13 years) healthy subjects were enrolled at 22 collaborating institutions of the Normal Reference Ranges for Echocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 37 publications
11
47
2
1
Order By: Relevance
“…22,23 The description of these changes has led to a more comprehensive understanding of reduced longitudinal strain of LV, as well as the decrease of GWI and GCW that could be supposed to re ect LV performance and mechanics globally. 11 In this study, compared with the control group, the reduction in GWI and GCW in the athlete group was not statistically signi cant, but suggested that the myocardial metabolism was decreased and LV systolic function was impaired to some extent. Signi cantly, increased PSD in the athlete group draw attention to the points that the systolic synchronization of LV had been destroyed and nonuniformity of ventricular wall motion would reduce the mechanical e ciency during cardiac ejection.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…22,23 The description of these changes has led to a more comprehensive understanding of reduced longitudinal strain of LV, as well as the decrease of GWI and GCW that could be supposed to re ect LV performance and mechanics globally. 11 In this study, compared with the control group, the reduction in GWI and GCW in the athlete group was not statistically signi cant, but suggested that the myocardial metabolism was decreased and LV systolic function was impaired to some extent. Signi cantly, increased PSD in the athlete group draw attention to the points that the systolic synchronization of LV had been destroyed and nonuniformity of ventricular wall motion would reduce the mechanical e ciency during cardiac ejection.…”
Section: Discussioncontrasting
confidence: 54%
“…9 The clinical values of this new approach have potential in predicting response to cardiac resynchronization therapy and assessing myocardial contractility in hypertension and dilated cardiomyopathy. 10,11 The purpose of this study aimed to: (i) describe the basic echocardiography characteristics of LV in the hearts of the athletes and (ii) explore the possibility of LVMW parameters to evaluate myocardial function among the athletes.…”
Section: Echocardiographic Analysismentioning
confidence: 99%
“…We measured the myocardial global work index (GWI-mmHg%) as the area under the curve from mitral valve closure to mitral valve opening using dedicated software (EchoPac PC 203, GE Healthcare, Horten, Norway) to construct pressure-LV longitudinal myocardial strain loop by speckle tracking echocardiography ( Ikonomidis et al, 2019a ; Manganaro et al, 2020 ). Furthermore, the software calculated the global constructive work (GCW-mmHg%) as work performed during shortening in systole adding negative work during lengthening in isovolumetric relaxation and the wasted myocardial work (GWW-mmHg%) as negative work performed during lengthening in systole adding work performed during shortening in isovolumetric relaxation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the software calculated the global constructive work (GCW-mmHg%) as work performed during shortening in systole adding negative work during lengthening in isovolumetric relaxation and the wasted myocardial work (GWW-mmHg%) as negative work performed during lengthening in systole adding work performed during shortening in isovolumetric relaxation. The constructive work divided by the sum of constructive and wasted work provides the global work efficiency (GWE-%) ( Manganaro et al, 2020 ). The inter- and intra-observer reproducibility for GWI were ≤8% and ≤9% respectively.…”
Section: Methodsmentioning
confidence: 99%
“…выявлена статистически значимая корреляция между показателями работы и деформационными характеристиками миокарда у 226 здоровых субъектов (45 ± 13 лет). Наибольшая корреляция наблюдалась между GCW и GLS (-0,55; p < 0,001) [41]. Интересные результаты представлены в исследовании E. Boe, где была продемонстрирована большая чувствительность и специфичность индекса регионарной работы миокарда (81 и 82%) против GLS (78 и 65% соответственно) в способности вывлять коронарную окклюзию у больных инфарктом миокарда без подъема сегмента ST [42].…”
Section: миокардиальная работа (мYocardial Work)unclassified